Developing Linguistic Abilities of Learners with “Cartoon Dubbing” Technique - V. Kulakova, Natalya; S. Spiridonova, Galina; V. Vekkesser, Maria; S. Shmul'skaya, Larisa; L. Rostova, Marina (International Journal of Psychosocial Rehabilitation, 2020)
Academic-information skills of modern schoolchildren imply the ability to work with written texts, the ability to work with oral texts, the ability to work with real objects as sources of information, the ability to identify and understand information transferred in explicit/implicit form, the ability to transfer the information essential for solving an academic task to an interlocutor/partner, and the ability to participate in a dialogue when discussing what had been read or listened to. Thus, the main objective of the paper is to describe the content of methodological work when using cartoon dubbing and to substantiate its efficiency. The technique creates conditions for developing all the above-mentioned skills in learners; it facilitates perception of information, develops creativity, and activates thinking and speech. The schoolchildren perceive the verbal and non-verbal information transmitted spontaneously. The technique enables the teacher to implement the activity- and personality-oriented approaches. We experimentally proved the technique's efficiency as a means of developing the linguistic abilities of the learners. As a result, we conclude that methodological work with the said technique is a part of media education for schoolchildren, which is essential in the modern world.